PAMALI DALAM KEHIDUPAN MASYARAKAT KAMPUNG ADAT JALAWASTU - Sulisthya Dewi; Ananda Cahya Camila; Siti Nurjanah; Decinta Nesa Karisma; Odien Rosidin; M. Rinzat Iriyansah; Robita Ika Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article discusses the taboos that exist in the lives of the community of the Jala wastu Traditional Village, Ciseureuh Village, Ketanggungan Subdistrict, Brebes Regency. This study aims to explain the various types of taboos and their function s in the lives of the locThis article discusses the taboos that exist in the lives of the community of the Jalawastu Traditional Village, Ciseureuh Village, Ketanggungan Subdistrict, Brebes Regency. This study aims to explain the various types of taboos and their functions in the lives of the local indigenous community. This study employs a descriptive qualitative method to collect data through various techniques such as interviews, observation, document collection, note-taking, recording, and listening. The findings of this study indicate that taboos in the Jalawastu Traditional Village encompass prohibitions related to infrastructure, animal husbandry, farming, playing musical instruments, dress codes, and entering areas considered sacred. Pamali are not only viewed as inherited traditions but also serve as mechanisms of social control, guidelines for behavior, and efforts to preserve culture and the environment. The community’s adherence to pamali signifies that traditional values and local wisdom are still preserved to this day amidst modern progress.